2018
DOI: 10.1007/s00784-018-2551-6
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect of bioceramic cements on multispecies microcosm biofilm: a confocal laser microscopy study

Abstract: NeoMTA Plus, Biodentine, and MTA Angelus were not effective against multispecies microcosm biofilm. It is essential to understand that these bioceramic cements are indicated for infected clinical situations. Thus, complementary disinfection procedures should be conducted prior to filling with these materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 38 publications
2
18
1
Order By: Relevance
“…29 Pompermayer et al found that MTA was not effective against multispecies microcosm biofilms including E. faecalis, Streptococcus salivarius (S. salivarius), Streptococcus mutans (S. mutans) and so on. 30 In this study, the E. faecalis biofilms treated with MTA was still intact, and the proportion of live bacteria was high, suggesting that MTA had no obvious antibacterial effect on E. faecalis biofilms, which was similar to previous studies. MCSNs has antibacterial effect on planktonic E. faecalis, but the antibacterial effect of MCSNs on E. faecalis biofilms is obviously lower than that of CH.…”
Section: Discussionsupporting
confidence: 90%
“…29 Pompermayer et al found that MTA was not effective against multispecies microcosm biofilms including E. faecalis, Streptococcus salivarius (S. salivarius), Streptococcus mutans (S. mutans) and so on. 30 In this study, the E. faecalis biofilms treated with MTA was still intact, and the proportion of live bacteria was high, suggesting that MTA had no obvious antibacterial effect on E. faecalis biofilms, which was similar to previous studies. MCSNs has antibacterial effect on planktonic E. faecalis, but the antibacterial effect of MCSNs on E. faecalis biofilms is obviously lower than that of CH.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the antimicrobial activity of the tested materials, neither formulation satisfactorily inhibited bacterial growth in comparison to direct contact with chlorhexidine 2% in both methods. Previous studies showed similar results for ProRoot MTA [30] and Biodentine [31] using other methods. Solubility halos were observed over agar, showing that this initial test seems to be inadequate due to possible misleading interpretation.…”
Section: Discussionsupporting
confidence: 66%
“…However, the results of the present study indicate that the type of repair material did have an effect on the viability of the colonizing bacteria, with significantly more live bacteria detected in the MTA-Angelus group than in the Endocem and Biodentine groups. This is in contrast to a previous study by Jardine et al (2019) who used confocal laser microscopy to evaluate the viability of a multispecies microcosm in the vicinity of bioceramic cements and concluded that MTA-Angelus was as effective as Biodentine in terms of antimicrobial activity [51]. This discrepancy may be explained by the different microorganisms involved.…”
Section: Discussioncontrasting
confidence: 79%